(untitled) (Voice: A Biannual & Bilingual Journal, 2024)
This study explores the marketing strategies and consumer perceptions of Patanjali Ayurveda Ltd, a rapidly growing FMCG brand in India. Through a survey of 50 Patanjali product users in Nepalgunj, the research found high customer satisfaction with the brand’s affordability and effectiveness. The study emphasizes the crucial role of Ramdev Baba’s brand image and continuous innovation in enhancing market share. It also identifies product shortages and limited distribution as key concerns. Recommendations for Patanjali include diversifying brand ambassadors, capitalizing on the organic sector’s growth, expanding its online presence, and targeting youth consumers. Addressing these areas can boost market presence, customer satisfaction, and overall business success. This research highlights Patanjali’s transition from a minor player to a leading FMCG giant since its 2006 inception, driven by low pricing, natural ingredients, and a strong Swadeshi position. Despite high consumer satisfaction, challenges like overreliance on Baba Ramdev and distribution issues must be addressed for sustained growth.